2019
DOI: 10.1177/2167479519876886
|View full text |Cite
|
Sign up to set email alerts
|

“I Can’t Stand Women’s Sports”: The Perception of Women’s Sports by Polish Sports Journalists

Abstract: This article analyzes the opinions of Polish male ( n = 18) and female ( n = 18) sports journalists on the representation of women’s sports in media coverage. The surveyed journalists represented journalists from national television stations, radio stations, and press and Internet media. Some of them were working simultaneously in various mass media outlets. In-depth interviews were conducted in various locations in Poland in 2018. An analysis of the journalists’ views from 36 semi-structured interviews indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…In previous studies, sports journalist were described as misogynist and reluctant to cover female athletes claiming they are not responsible for the improvement of gender equality (Knoppers and Elling, 2004 ; Organista et al, 2021 ). In other studies, journalists who claimed fair agenda were contradicted by the actual content analysis (Billings, 2009 ; Xu, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, sports journalist were described as misogynist and reluctant to cover female athletes claiming they are not responsible for the improvement of gender equality (Knoppers and Elling, 2004 ; Organista et al, 2021 ). In other studies, journalists who claimed fair agenda were contradicted by the actual content analysis (Billings, 2009 ; Xu, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main findings show that personal influence had a significant influence on the provided content. However, unlike the news media (Organista et al, 2021 ), the media personnel identified themselves with the Olympic values and commitment to gender equality and women's empowerment. Consequently, it resulted in fairer portrayal of female athletes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…At this point it is worthwhile to briefly shift the focus to production studies in sport media concentrating on gender. This is relevant as -in contrast to the relatively few production studies on race/ethnicity -there is a relatively larger number of production studies with a focus on social identities other than race/ethnicity in sport media such as (dis)ability (Howe, 2008), homosexuality (Kian et al, 2015), and above all, gender (see: Harden & Shain, 2005;Organista et al, 2019;Schoch, 2013). When surveying the literature on gender in sport media, it becomes clear that (overwhelmingly White and male) producers and journalists tend to rely on similar discursive strategies to explain stereotypical representations of female athletes, and the role sport media can play to challenge these representations, as those that have been noted in reference to race/ethnicity.…”
Section: Intersections With Production Studies On Gender In Sport Mediamentioning
confidence: 99%
“…Previous studies into gender and sport media found that journalists often relied on discursive strategies that prioritized 'objectivity', 'neutrality' and 'audience interest' to explain gendered inequities in sports reporting (Gee & Leberman, 2011;Knoppers & Elling, 2004;Organista et al, 2019). Knoppers and Elling (2004: 69-70) explain how such invoking of terms as "objectivity" and "neutrality" by sports journalists "work to secure consent to the point where conflicts of interest are not apparent and their power is seen as legitimate" and "to conceal issues of gendered dynamics of power, by using an ideology of neutrality".…”
Section: Intersections With Production Studies On Gender In Sport Mediamentioning
confidence: 99%